Core 2 ß1, 6-N-acetylglucosaminyltransferase-I, crucial for P-selectin ligand expression is controlled by a distal enhancer regulated by STAT4 and T-bet in CD4+ T helper cells 1. (September 2016) - Mardahl, Maibritt; Schröter, Micha F.; Engelbert, Dirk; Pink, Matthias; Sperandio, Markus; Hamann, Alf; Syrbe, Uta
Highlights: Core 2 ß1, 6-N-acetylglucosaminyltransferase-I ( Gcnt1 ) is required for P-selectin ligand (P-lig) synthesis and inflammatory homing of T helper 1 (Th1) cells. Gcnt1 expression in Th1 cells is controlled by a distal enhancer. Gcnt1 is induced by T cell receptor signaling and STAT4 and T-bet binding to the enhancer. Gcnt1 repression corresponds to H3K27me3 marks within the enhancer. Abstract: P-selectin ligands (P-ligs) support the recruitment of lymphocytes into inflamed tissues. Binding to P-selectin is mediated by oligosaccharide groups synthesized by means of several glycosyltransferases including core 2 ß1, 6- N -acetylglucosaminyltransferase-I (C2GlcNAcT-I), encoded by the gene Gcnt1. Using Gcnt1 −/− Th1 cells, we show that C2GlcNAcT-I is crucial for inflammatory T cell homing in vivo. To understand the molecular regulation of Gcnt1 in CD4 + T helper cells, we performed ChIP-on-chip experiments across the Gcnt1 locus assessing the chromatin structure in P-lig-expressing versus non-expressing CD4 + T cells. This identified a distal region about 20 kb upstream of the promoter where the presence of a H3K27me3 mark correlated with Gcnt1 repression. This region possessed IL-12-dependent enhancer activity in reporter assays, in accordance with preferential IL-12-dependent induction of Gcnt1 in vitro . STAT4 and T-bet cooperated in control of the enhancer activity. Deficiency in either one resulted in drastically reduced Gcnt1 mRNA expression in differentiated Th1 cells. While both STAT4 and T-bet were bound to the enhancer early after activation only T-bet binding persisted throughout the expansion phase after TCR signal cessation. This suggests sequential action of STAT4 and T-bet at the enhancer. In summary, we show that Gcnt1 transcription and subsequent P-lig induction in Th1 cells is governed by binding of STAT4 and T-bet to a distal enhancer and further regulated by epigenetic marks such as H3K27me3.